Even- and odd-chain saturated fatty acids in serum phospholipids are differentially associated with adipokines - Kurotani, Kayo; Sato, Masao; Yasuda, Kazuki; Kashima, Kentaro; Tanaka, Shoji; Hayashi, Takuya; Shirouchi, Bungo; Akter, Shamima; Kashino, Ikuko; Hayabuchi, Hitomi; Mizoue, Tetsuya (PLOS ONE, 2017)
Background Saturated fatty acids are generally thought to have detrimental effects on health. However, a recent study showed that even- and odd-chain saturated fatty acids had opposite associations with type 2 diabetes. Limited studies of Western populations examined the associations of circulating saturated fatty acids with adipokines, an important role in glucose metabolism. Objective We examined the associations of saturated fatty acids in serum phospholipids with circulating levels of adipokines among a Japanese population. Design A cross-sectional study was conducted among 484 Japanese employees (284 men and 200 women) aged 20–65 years. The serum fatty acid composition in the phospholipid fraction was measured by gas-chromatography. Serum leptin, adiponectin, plasminogen activator inhibitor-1 (PAI-1), resistin, and visfatin were measured using a Luminex suspension bead-based multiplexed array. Multiple linear regression analysis was performed to assess the association between saturated fatty acids and adipokines, with adjustment for potential confounding variables. Results Even- and odd-chain saturated fatty acids were differentially associated with adipokines. Higher levels of even-chain saturated fatty acids (14:0 myristic, 16:0 palmitic, and 18:0 stearic acids) were associated with higher levels of resistin (P for trend = 0.048) and lower levels of adiponectin (P for trend = 0.003). By contrast, odd-chain saturated fatty acids (15:0 pentadecanoic and 17:0 heptadecanoic acids) showed inverse associations with leptin and PAI-1 (P for trend = 0.048 and 0.02, respectively). Visfatin was positively associated with both even- and odd-chain saturated fatty acids. Conclusions The results suggest that even- and odd-chain saturated fatty acids are differentially associated with adipokine profile.